Specifying Training Need through Occupational Competency Analysis Required for Coaches for Physically Challenged Athletes in Water According to International Standards ISO 10015 - Ibrahim, Amal Mohamed; Aswad, Khalid; Ahmed, Salima Hassan (Journal of Physical Education, 2023)
The research aimed at analyzing training needs for theoretical, field and practical competencies related to the safety of trainers and trainees as well as for active communication with athletes suffering from water disability before, during and after training. The research also aimed at evaluating the degree of occupational competencies concluded in this research. The researchers used the descriptive method on forming a questionnaire on (84) individuals. The results showed that coaches and trainers’ safety and health competency should be 98% followed by water therapeutic exercises competency using aiding tools and apparatuses 97% then therapeutic programs design competency 95%, then finally diagnostic tests and hydrotherapy 93%. The researchers recommended using these competencies as guidelines for training medical personals and graduates from colleges of physical education and sport sciences.